Silica Removal of Oil Palm Empty Fruit Bunch Fiber - Hapip Ramadhan; Jaroslav Stavik; Yin Ying Hng; Moh Fahrurrozi (International Journal of Technology, 2024)
This research aimed to optimize sodium hydroxide concentration and temperature in silica removal of oil palm empty fruit bunch (EFB) fiber. The process began with extensive washing of fiber at 3% consistency and a temperature of 50°C using warm water before alkaline treatment to eliminate external silica, reducing the concentration from 7683 ppm to 5294 ppm. This initial step caused a decrease in total yield by removing non-fiber material and short carbohydrates. Despite the significant material loss, the byproduct showed promising potential for further use as fertilizer. The washing stage was followed by alkali treatment when different dosages of caustic and temperature were optimized based on design experiments using 22 factorial designs and regression modeling. The optimum alkali treatment condition was set at 60°C and NaOH concentration of 0.05 M, resulting in EFB-treated yield of 90.6 % with silica content of approximately 3000 ppm as acid-insoluble ash.